The Influence of Human Resource Policy and Development on Security Performance at the Cimanggis Military Detention Installation - Muhammad Sastra Anafera; Yuni Pratikno; Jamal Hanaffy (Dinasti International Journal of Digital Business Management, 2026)
Security and development at military detention facilities are strategic aspects that require effective policy support and continuous human resource development to ensure optimal and sustainable security performance. The Cimanggis Military Detention Facility has complex task characteristics, thus requiring professional personnel and policies that are able to accommodate operational dynamics and detainee development. This study aims to analyze the influence of policy effectiveness and human resource development on security performance at the Cimanggis Military Detention Facility, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to 96 personnel at the Cimanggis Military Detention Facility as research respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that partially policy effectiveness has a positive and significant effect on security performance with a t-value of 4.277 and a significance level of 0.004. In addition, human resource development also has a positive and significant effect on security performance with a t-value of 4.414 and a significance level <0.001. Simultaneously, the effectiveness of policies and human resource development have a significant effect on security performance at the Cimanggis Military Detention Installation, as indicated by the F-value of 27.219 with a significance of <0.001. The coefficient of determination (R Square) of 0.369 indicates that the two independent variables are able to explain 36.9% of the variation in security performance, while the remaining 63.1% is influenced by other factors outside the research model. This finding confirms that increasing policy effectiveness supported by planned, systematic, and sustainable human resource development is an important factor in strengthening security performance at the Cimanggis Military Detention Installation